Developing and evaluating a predictive model for neonatal hyperbilirubinemia based on UGT1A1 gene polymorphism and clinical risk factors - Cui, Zhaoyang; Shen, Wensheng; Sun, Xuetong; Li, Yan; Liu, Ying; Sun, Zhiyong (Frontiers in Pediatrics, 2024)
Neonatal hyperbilirubinemia (NHB) is one of the most common diseases in the neonatal period.Without timely diagnosis and treatment, it can lead to long-term complications. In severe cases, it may even result in fatality. In this study, we used the cohort study, and clinical risk factors and the polymorphism of G211A locus of UGT1A1 gene of newborns were used to develop and evaluat a predictive model. We retrospectively analyzed 3258 newborns from the Jilin Women And Children Health Hospital in northern China, including 372 children with hyperbilirubinemia. Logistic regression model was employed to create a predictive model with eight significant factors, such as neonatal gestational age, the time when stool turns yellow, mode of delivery, neonatal cephalohematoma, hemolytic disease of the newborn, neonatal weight loss, neonatal premature rupture of membranes history, and the G211A locus polymorphism of the UGT1A1 gene.The area under the curve (AUC) of this prediction model is 0.804(95% CI: 0.777-0.831). We utilized the results of UGT1A1 gene polymorphism to construct a nomogram for the first time, which can more intuitively and better predict the onset of neonatal hyperbilirubinemia, thereby reducing the disease burden and long-term impact of neonatal hyperbilirubinemia.